Pure Intralymphatic Invasion in the Absence of Stromal Invasion After Neoadjuvant Therapy: A Rare Pattern of Residual Breast Carcinoma. (May 2018) - Guilbert, Marie-Christine; Overmoyer, Beth; Lester, Susan C.
Abstract : Rarely is intralymphatic/lymph-vascular invasion (LVI) the only residual disease in the breast after neoadjuvant chemotherapy. Only 12 patients have been reported in 2 prior studies. Prognosis was poor, with only 2 patients remaining alive and disease-free. The purpose of this study was to gather more data on this pattern of residual disease. Cases in which LVI was the only residual disease in the breast were retrospectively identified. Eighteen cases were identified including 10 of 669 (1.5%) consecutive surgical cases between 2003 and 2015. The mean tumor size was 3.4 cm. Seven cancers were negative for estrogen receptor and HER2, 8 were HER2 positive, and 3 were estrogen receptor positive and HER2 negative. In 15 cases, lymph nodes were either suspicious by imaging or proven positive by biopsy. After neoadjuvant chemotherapy, 9 patients were node negative, 7 were node positive, and 2 had isolated tumor cells. Mean follow-up was 63.8 months (7 to 138 mo). Two deaths occurred in patients with positive nodes. One death occurred and 2 patients are alive with metastatic disease in the node-negative group. The remaining 13 patients are alive without disease. The outcome associated with residual LVI might not be as dismal as previously reported. Although the better outcome may be due to stage at presentation or the type of chemotherapy, it is difficult to compare the cohorts of the 3 studies. However, the death of 3 of 13 node-negative patients over the 3 studies supports not classifying residual LVI as a pathologic complete response.